GY II represses proliferation and metastasis and promotes apoptosis in laryngeal squamous cell carcinoma. Issue 1 (2019) - Bai, Yunfei; Wang, Ru; Cui, Xiaobo; Feng, Lin; Shi, Qian; Ma, Hongzhi; Lian, Meng; Shen, Xixi; Yang, Yifan; Tan, Chen; Fang, Jugao
No abstract available